K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

14 tháng 7 2021

\(x^4-25=0\)

\(\Leftrightarrow x^4=25\)

\(\Leftrightarrow x^2=5\)

\(\Leftrightarrow x=\sqrt{5}\)

#H

14 tháng 7 2021

x=\(\sqrt{5}\)

ai k cho mình

nhắn mình mình k lại!

19 tháng 10 2016

a, x^2(x^2+4)-x^2-4=0

=) x^2(x^2+4)-(x^2+4)=0

=) (x^2+4)(x^2-1)=0

=)(x^2+4)(x-1)(x+1)=0

=) x^2+4=0 =)x^2=4 =)x=2

    x-1=0 =)x=1

    x+1=0 =)x=-1

b,x^2-25-x-5=0

=)(x+5)(x-5)-(x+5)=0

=)(x+5)(x-6)=0

=)x+5=0  =) x=-5

   x-6=0   =) x=6

8 tháng 10 2019

         4 - 25x= 0

\(\Rightarrow\)25x2 = 4

\(\Rightarrow\)x2 = 4 / 25

\(\Rightarrow\)x   = \(\pm\)( 2 / 5 )2

27 tháng 7 2017

x2 - 4 = 0

x2 = 4

\(\orbr{\begin{cases}x^2=2^2\\x^2=\left(-2\right)^2\end{cases}}\)

\(\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)

3x2 - 75 = 0

3x2 = 75

x2 = 25

\(\orbr{\begin{cases}x^2=5^2\\x^2=\left(-5\right)^2\end{cases}}\)

\(\orbr{\begin{cases}x=5\\x=-5\end{cases}}\)

( x + 2 )2 = 25

\(\orbr{\begin{cases}\left(x+2\right)^2=5^2\\\left(x+2\right)^2=\left(-5\right)^2\end{cases}}\)

\(\orbr{\begin{cases}x+2=5\\x+2=-5\end{cases}}\)

\(\orbr{\begin{cases}x=3\\x=-7\end{cases}}\)

6 tháng 6 2016

a, \(x^2-25-\left(x+5\right)=0\)

\(\Rightarrow x^2-5^2-\left(x+5\right)=0\)

\(\Rightarrow\left(x-5\right)\times\left(x+5\right)-\left(x+5\right)=0\)

\(\Rightarrow\left(x+5\right)\times\left(x-5-1\right)=0\)

\(\Rightarrow\left(x+5\right)\times\left(x-6\right)=0\)

\(\Rightarrow\hept{\begin{cases}x+5=0\\x-6=0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}x=0-5=\left(-5\right)\\x=0+6=6\end{cases}}\)

b, \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)

\(\Rightarrow\left(2x-1\right)^2-\left(\left(2x\right)^2-1^2\right)=0\)

\(\Rightarrow\left(2x-1\right)^2-\left(2x-1\right)\times\left(2x+1\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(2x-1-\left(2x+1\right)\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(2x-1-2x-1\right)=0\)

\(\Rightarrow\left(2x-1\right)\times\left(-2\right)=0\)\(\Rightarrow\left(-4x\right)+2=0\)

\(\Rightarrow\left(-4x\right)=0-2=-2\)

\(\Rightarrow x=\frac{-2}{-4}=\frac{1}{2}\)

c, \(x^2\times\left(x^2+4\right)-x^2-4=0\)

\(\Rightarrow x^2\times\left(x^2+4\right)-\left(x^2+4\right)=0\)

\(\Rightarrow\left(x^2-1\right)\times\left(x^2+4\right)=0\)

\(\Rightarrow\hept{\begin{cases}x^2-1=0\\x^2+4=0\end{cases}}\)

\(\Rightarrow\hept{\begin{cases}x^2=1\\x^2=\left(-4\right)\end{cases}}\)

\(\Rightarrow x=1\)

17 tháng 8 2019

\(x^2-3x=0\)

\(\Leftrightarrow x\left(x-3\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)

17 tháng 8 2019

\(x^5-9x=0\)

\(\Leftrightarrow x\left(x^4-9\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x^4-9=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt[4]{9}\end{cases}}\)

21 tháng 10 2016

8x2+30x+7=0

 8x2+16x+14x+7=0

8x(x+2) +7(x+2)=0

(8x+7)(x+2)=0

=>\(\orbr{\begin{cases}8x+7=0\\x+2=0\end{cases}\Rightarrow\orbr{\begin{cases}x=-\frac{7}{8}\\x=-2\end{cases}}}\)

21 tháng 10 2016

a)

4x2-8x+4=2(1-x)(x+1)

4x2-8x+4-2+2x2=0

6x2-8x+2=0

2(3x2-4x+1)=0

3x2-3x-x+1=0

3x(x-1) -(x-1)=0

(3x-1)(x-1)=0

\(\Rightarrow\orbr{\begin{cases}3x-1=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=\frac{1}{3}\\x=1\end{cases}}}\)